Degrowth and progress: a critical genealogy and contemporary analysis of growthism - Miller-Mcdonald, S (2023)

(untitled)
This thesis interrogates the relationship between growth—using an expanded definition of the economic concept to mean an ecologically exclusionary mode of sociotechnical metabolism predicated on extraction and expansion—and progress, a metanarrative that facilitates political rhetorics co-reproducing growth. This thesis suggests that Anthropocenic challenges like inequalities in the distribution of human well-being indicators and global ecological harms can be understood as emerging from the historical trajectory of growth, the metaideology (“growthism”) that has arisen to systematize and operationalize it, and the metanarrative of progress that has co-reproduced it. As such, the study begins with a (non-Foucauldian) genealogy tracing the lineage of the idea of progress and its relationship to forms of growth(ism) that arose in the Early Dynastic Period in Mesopotamia. Using this lineage, based on Western sources and history, as context, the study then interrogates contemporary attitudes, values, and motivations among practitioners of political, social, and technological change as they relate to growth, degrowth—the discipline and tendency recently risen to critique growth—and narratives of progress. This analysis focuses on materials gathered from in-depth interviews with practitioners. The study finds patterns emerging through time in the relationship between modes of growth and narratives of progress that offer productive insights for degrowth—or “post-growth”—literature and Anthropocene dating. Further, the study finds patterns in practitioners’ receptiveness to growth, degrowth, and progress that yield productive insights for degrowth scholarship and activism.